The Effect of Environmental Performance on Firm Performance Mediated by Green Innovation in Food Processing Industry Companies in the Special Region of Yogyakarta - Irfan, Muhammad; Sabihaini, Sabihaini; Effendi, Irhas (Technium Social Sciences Journal, 2023)
This study aims to determine the effect of environmental performance on firm performance and green innovation as mediator in food processing industry companies in the Special Region of Yogyakarta. The type of research used is hypothesis testing with quantitative methods. The sampling technique in this research was non-probability sampling with a purposive sampling technique. The considerations or criteria determined in this study are food processing companies with large and medium scale. The number of samples used in this study were 60 companies. Testing in this study was assisted by the SmartPLS 3.3.3 software. And the results obtained are as follows: Environmental performance has a positive and significant effect on green innovation in the food processing industry in the Special Region of Yogyakarta; Environmental performance has a positive and significant effect on firm performance in the food processing industry in the Special Region of Yogyakarta; Green innovation has a positive and significant effect on company performance in the food processing industry in the Special Region of Yogyakarta; and environmental performance has a positive and significant effect on company performance through green innovation in the food processing industry in the Special Region of Yogyakarta.